Exploring Biosynthetic Diversity with Trichodiene Synthase, - Vedula, L. Sangeetha (2007)
Trichodiene synthase is a terpenoid cyclase that catalyzes the cyclization of farnesyl diphosphate (FPP) to form the bicyclic sesquiterpene hydrocarbon trichodiene (89%), at least five sesquiterpene side products (11%), and inorganic pyrophosphate (PP(i)). Incubation of trichodiene synthase with 2-fluorofarnesyl diphosphate or 4-methylfarnesyl diphosphate similarly yields sesquiterpene mixtures despite the electronic effects or steric bulk introduced by substrate derivatization. The versatility of the enzyme is also demonstrated in the 2.85 Å resolution X-ray crystal structure of the complex with Mg(2+) (3)-PP(i) and the benzyl triethylammonium cation, which is a bulkier mimic of the bisabolyl carbocation intermediate in catalysis. Taken together, these findings show that the active site of trichodiene synthase is sufficiently flexible to accommodate bulkier and electronically-diverse substrates and intermediates, which could indicate additional potential for the biosynthetic utility of this terpenoid cyclase.